2021
DOI: 10.3390/su13084548
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Corporate Social Responsibility Execution Effects on Purchase Intention with the Moderating Role of Customer Awareness

Abstract: Corporate social responsibility (CSR) in management domains is a well-known concept that links corporate interests and environmental/community values. CSR is considered a strategic policy that offers environmental and social competitive advantages. Organizations consider that CSR-based goodwill provides a tactical competitive edge and sustainable growth. The goal of this paper is to show how CSR programs affect consumers’ purchasing intention in the context of Pakistan. In addition, the effect of customer awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 130 publications
(163 reference statements)
5
42
0
Order By: Relevance
“…The study has provided the statistical evidence for supporting the significantly positive effect of ECSR initiatives on intention to engage in pro-environmental consumption among Vietnamese consumers. This finding was also consistent with several recent studies (Munerah et al , 2021; Martínez García de Leaniz et al , 2019; Zhang and Ahmad, 2021). It means that consumers with high perceptions of ECSR initiatives can have higher intentions to buy green products.…”
Section: Discussionsupporting
confidence: 94%
“…The study has provided the statistical evidence for supporting the significantly positive effect of ECSR initiatives on intention to engage in pro-environmental consumption among Vietnamese consumers. This finding was also consistent with several recent studies (Munerah et al , 2021; Martínez García de Leaniz et al , 2019; Zhang and Ahmad, 2021). It means that consumers with high perceptions of ECSR initiatives can have higher intentions to buy green products.…”
Section: Discussionsupporting
confidence: 94%
“…Chu and Chen ( 2019 ) find that consumers' participation in CSR-related activities in social media promotes purchase intention through enhancing identification with the brand and positive brand attitude. Zhang and Ahmad ( 2021 ) discover that CSR affects consumers' purchase attention through trust and brand image.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Several studies suggested that these kinds of expenditures and socially responsible operation of the firm affect corporate reputation (Peterson, 2018), customer purchase decisions (Zhang and Ahmad, 2021), firm performance (Fourati and Dammak, 2021) and firm value (Chung et al, 2018). Therefore, the amount spent on the account of CSR has a significant effect on corporate reputation which further increases the purchase likelihood of a product ending with better firm performance, and it also builds the CA (Shah and Khan, 2019).…”
Section: Hypothesis Developmentmentioning
confidence: 99%